The protrayal of women in television advertisements on SABC3: a reflection on stereotypical representation - Pillay, Nerisa (My University, 2010)
ABSTRACT This study involves an analysis of sampled television advertisements drawn from SABC3. The aim of this study is to explore the ways that female characters are portrayed in South African advertising content and to compare this with how male characters are portrayed. This has been undertaken through a quantitative and qualitative analysis of the advertisements in order to indentify themes and patterns in the representation of women and men. The premise of this study is that female characters are stereotyped resulting in a limited view of women in advertising content. Upon examination of the advertisements it was found that female characters are still stereotyped and portrayed in line with traditional roles associated with women, while a more significant change was found in how male characters are portrayed. In conducting this analysis, this study highlights the importance of continued research in the field of gender studies as a means of measuring the media’s representation of women against social change and development.